2009
DOI: 10.1007/s12540-009-0765-x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nanopowder and consolidation of nanocrystalline 5Ni0.6Fe0.4-Al2O3 composite by rapid sintering

Abstract: Nano-powders of 5Ni 0.6 Fe 0.4 and Al 2 O 3 were synthesized from 3NiO and 2FeAl powders by high energy ball milling. Nanocrystalline 5Ni 0.6 Fe 0.4 -Al 2 O 3 composite was consolidated by pulsed current activated sintering method within 2 min from mechanically alloyed powders of Al 2 O 3 and 5Ni 0.6 Fe 0.4 . The average hardness and fracture toughness values obtained were 990 kg/mm 2 and 7.5 MPa·m 1/2 , respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…[12,[16][17][18][19][20][21][22][23][24][25][26][27] Wang et al [16] reported that the fracture toughness of Ni-Mn-Ga-Fe alloys increased with increasing the Fe content by the fracture mode change from intergranular to transgranular. However, improvement of fracture properties of ferromagnetic shape memory alloys by particle distribution in relation to the microstructural modification was only rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…[12,[16][17][18][19][20][21][22][23][24][25][26][27] Wang et al [16] reported that the fracture toughness of Ni-Mn-Ga-Fe alloys increased with increasing the Fe content by the fracture mode change from intergranular to transgranular. However, improvement of fracture properties of ferromagnetic shape memory alloys by particle distribution in relation to the microstructural modification was only rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] There have been several successful examples of its use. Song et al 11) established the thermodynamic basis of YAG fabrication by combustion synthesis through a study of the adiabatic temperature of many aluminothermic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Combustion synthesis, called self-propagating high-temperature synthesis (SHS), [9][10][11] can generate high temperatures without requiring alternative energy sources. For example, the adiabatic temperatures of NiO/Al and Fe 2 O 3 /Al aluminothermic systems reach 3524 K and 3622 K, respectively, which are above the melting points of products investigated thus far in the literature.…”
Section: Introductionmentioning
confidence: 99%